2006
DOI: 10.1002/cncr.22442
|View full text |Cite
|
Sign up to set email alerts
|

Partial volume tolerance of the spinal cord and complications of single‐dose radiosurgery

Abstract: BACKGROUND.Spine radiosurgery causes a rapid dose fall‐off within the spinal cord. The tolerance of partial volume of the spinal cord may determine the extent of clinical application. The study analyzed the partial volume tolerance of the human spinal cord to single fraction radiosurgery.METHODS.A total of 230 lesions with spine metastases in 177 patients were treated with radiosurgery with single fraction of 8 to 18 Gy, prescribed to the 90% isodose line that encompassed the target volume. Spinal cord volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
150
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(155 citation statements)
references
References 25 publications
3
150
0
Order By: Relevance
“…The risks of radiation myelopathy in spinal SRS/SBRT were very well studied6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 with Dmax been generally accepted as the parameter of dosimetric constraint. Kirkpatrick et al summarized nine published reports of spinal cord dose and myelopathy in 1,400 patients who received spinal SRS/SBRT 16.…”
Section: Discussionmentioning
confidence: 99%
“…The risks of radiation myelopathy in spinal SRS/SBRT were very well studied6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 with Dmax been generally accepted as the parameter of dosimetric constraint. Kirkpatrick et al summarized nine published reports of spinal cord dose and myelopathy in 1,400 patients who received spinal SRS/SBRT 16.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal cord was delineated on a planning CT scan after fusion with an MRI or CT myelography. The partial spinal cord and partial spinal cord PRV was limited to 6 mm above and below the PTV (19) . Depending on the location of the vertebrae and the PTV, other organs at risk (OAR) that were segmented included liver, lungs, esophagus, bowel, skin, large vessels, and kidneys.…”
Section: Methodsmentioning
confidence: 99%
“…39 The median total radiation dose was 24 Gy (range, 18-35 Gy), in a mean of 3 fractions (range, 1-5). With a median follow-up for the cohort of 13 months (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], local control based on imaging was achieved in 7 of the 10 patients treated.…”
Section: High-dose Spinal Rt In the Adjuvant Settingmentioning
confidence: 99%
“…Other studies have suggested that the spinal cord can tolerate at least a single dose of 10 Gy to 10% of the cord segment that is adjacent to a targeted tumor plus 6 mm above and below this segment, with a risk of radiation-induced myelopathy of <0.5%. 16 Sahgal et al reported Dose-Volume Histograms (DVH) of nine patients who developed radiation myelopathy post-SBRT and compared them with a cohort of 66 spine SBRT patients who did not develop the toxicity. 17 A logistic regression model was developed to establish the probability of myelopathy using the thecal sac point maximum (Pmax) volume.…”
mentioning
confidence: 99%